SBRT in operable early stage lung cancer patients - Roesch, Johannes (Transl Lung Cancer Res, 2014)
Since decades the gold standard for treatment of early stage non-small cell lung cancer (NSCLC) is surgical lobectomy plus mediastinal lymph node dissection. Patients in worse health status are treated with sublobar resection or radiation treatment. With development of stereotactic-body-radiotherapy (SBRT), outcome of patients treated with radiation was substantially improved. Comparison of SBRT and surgical techniques is difficult due to the lack of randomized trials. However, all available evidence in form of case control studies of population based studies show equivalence between sublobar resection and SBRT indicating that SBRT—when performed by a trained and experienced team—should be offered to all high-risk surgical patients. For patients not willing to take the risk of lobectomy and therefore refusing surgery, SBRT is an excellent treatment option.